The Effects of Iron-Bearing Minerals on the Community Diversity and Physiological Activity of Prokaryotic Microorganisms in Pit Mud Used for Strong-Flavor baijiu Production - Kairui Jiao; Bo Deng; Ping Song; Liwei Wang; Bin Lian (Foods)
The quality of strong-flavor baijiu largely depends on the physicochemical properties and prokaryotic microbial activities of pit mud. However, the impact of the iron-bearing minerals in pit mud on its prokaryotic microbial communities remains unknown. This study examined the differences in the prokaryotic communities between 2-year, 40-year, and 100-year pit mud and yellow soil (the raw material for pit mud), as well as the impacts of environmental factors, particularly iron-bearing minerals, on the structure and diversity of these prokaryotic communities. The results indicated that there were significant differences in the composition of prokaryotic microorganisms between yellow soil and pit mud. As the fermentation pit aged, the relative abundance of dominant fermentation bacteria (including Petrimonas, Syntrophomonas, Clostridium, etc.) and hydrogenotrophic methanogens in the pit mud increased. The relative abundance of Lactobacillus in the 2-year pit mud was low (0.33%). Under laboratory conditions, goethite (a typical crystalline iron mineral, denoted as Fec) reduced the physiological and metabolic activity of Lacticaseibacillus paracasei JN01 in a concentration-dependent manner. The results of the physicochemical analysis showed that the contents of total iron (TFe) and Fec significantly decreased, while the contents of Fe(II) and amorphous iron (hydr)oxides (Feo) significantly increased with an increasing fermentation pit age. TFe and Fec were significantly negatively correlated with both the Chao1 and Shannon indexes and functional microorganisms such as Clostridium_sensu_stricto_12, Sedimentibacter, and hydrogenotrophic methanogens. The current results contribute to our understanding of the aging process of pit mud from the perspective of the interaction between iron-bearing minerals and prokaryotic microorganisms.